#HuelgaUPR: The Kidnapping of the University of Puerto Rico, Students Activism, and the Era of Trump - Martinez, Andrew; Garcia, Nichole M. (Frontiers in Education, 2018)
For the past 100 years, Puerto Rico as an unincorporated territory of the United States, has experienced economic hardship. In 2016, President Barack Obama signed into law a bill known as PROMESA (promise) to assist Puerto Rico in the reconstruction of the economy hoping to relieve the island from its 74 billion dollar debt. PROMESA proposed to cut funds to the island's university system totaling roughly 450 million over 3 years. In the wake of the presidential administration changing from President Barack Obama to Donald Trump, Puerto Rico filed for bankruptcy. The University of Puerto Rico (UPR), the main public university system of the island, has become a site of protests and strikes for students due to proposed cuts in the fiscal plan submitted by Gov. Ricardo Rosselló Nevares to the Fiscal Oversight and Management Board. All the universities in the UPR system are considered Hispanic Serving Institutions (HISs), producing college graduates that work on the island, but also stateside contributing to the United States economy. This study examines the #HuelgaUPR (strike UPR), created by student activists that attend college in UPR system. We examine newspapers (local and national), and Twitter as primary documents to understand student demands, UPR, and government responses to those demands. Through a content analysis, which is the study of sign systems intersecting with power, we seek to understand the activism that has always been a part of the culture within the UPR system. Our analysis uses Chicana/Latina feminist cultural studies (FCS) and the four tenets: intersectionality and global solidarity, breaking down dualisms, the embracing of ambiguity, and the project of tracking decolonial agency. Our findings suggests that #HuelgaUPR movement illuminates how student activism issues of free speech have proliferated since the election of Trump, and how the students of UPR resist the “kidnapping” of their institution through civil disobedience and the use of social media.